ADVERSE DRUG REACTIONS IN CRIMEA REPUBLIC IN 2013 - O. I. Koniaieva; O. V. Matvieiev (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2022)
In this article authors analyze patterns of ADRs registered in Crimea Republic in 2013. Data of ADR-reporting forms sent in 2013 by Crimean 21 doctors to Regional office of pharmacovigilance used. Information was recorded in local electronic database called "ARCADe". 1129 reports from 89 clinics had been analyzed. Most frequently ADRs were found in patients from 46 to 60 years old (22%) and in first year babies (8%). Among adults females suffered from MP ADRs more than males (61%), but among children boys dominated (58%). Most frequent type of serious ADR (37%) was life-threating ones and those, which led to hospitalization. Two reports informed about lethal reactions caused by Ceftriaxone and combination "Pitofenon+Metamizole-sodium". Causalityassessment revealed that bigger part of ADRs had belonged to "probable" type(43%). During risk factors analysis, we found complicated allergy anamnesis(10%) and polypharmacy (5% of cases). In 22% and 17% of reports, suspended MPswere prescribed for respiratory diseases and cardiologic pathologies treatment(respectively), and in 10% of cases for therapy of infections. Leading clinicalpresentation of ADR was skin rashes with different manifestations, severityand localization (50%), symptoms of involvement of CNS (11%), GIT and bloodcirculation system (7% both) were registered less frequently. In 5% of reports, wefound descri ption of angioneurotic edema and in 1% - symptoms of anaphylacticshock. 68% of ADRs required additional prescri ption of drugs for correctionof reaction`s symptoms. 39% of ADRs were caused by systemic antimicrobialproducts, 13% and 11% by MP influencing on functions of heart and CNS(respectively). In antibiotics group Cephalosporins prevailed and Ceftriaxonecaused most of ADRs, "Zidovudine+Lamivudine" combination was leading inantiretroviral drugs, among cardiological drugs ACE inhibitors prevailed butleading drug was Amplodi pine, and among NSAIDs most reactions were causedby Metamizole-sodium and its combinations. Conclusions. In 2013, the patterns ofADRs in Crimea region did not change and were the same as in previous years.Pharmacovigilance activity is high and amount of received reports satisfies WHOrequirements. Found patterns will ease formation of local and national strategyfor prevention of ADRs